Rehabilitation of Perak traditional house: repurposing Rumah Tok Sedara Bongsu into edutourism centre - Zabidi, Muhammad Amir Nasrullah; Ab Jalil, Nurlelawati (International Islamic University Malaysia, 2024)
Rumah Kutai is an old Perak traditional architecture that has become extinct due to modernisation and lacking proper preservation and conservation efforts. According to the National Heritage Act no. 645 standard, to overcome the issue and sustain its architectural heritage, the traditional building needs to be properly restored before being repurposed. This study aims to revitalise abandoned traditional houses, notably Rumah Tok Saudara Bongsu in Perak Tengah, with a dual purpose: conserving cultural and heritage values and transforming them into Perak pottery educational and tourism centre. Methodologically, this study employs two case studies: one for assessing dilapidation studies and another for designing a traditional pottery edutourism. The findings advocate a comprehensive approach. The main facades must be preserved to maintain the building's identity; dilapidated materials and areas necessitate restoration according to the standard, and additional face-lift, including additional spaces are proposed to support the new functions of the building with minimal disruptions. The study is significant to enhance the lifelong span of the house with proper conservation approaches. Besides, it promotes new function of the building for the public towards sustainable Perak cultural heritage.